2020
DOI: 10.3390/cells9102206
|View full text |Cite
|
Sign up to set email alerts
|

Disharmonic Inflammatory Signatures in COVID-19: Augmented Neutrophils’ but Impaired Monocytes’ and Dendritic Cells’ Responsiveness

Abstract: COVID-19, caused by SARS-CoV-2 virus, emerged as a pandemic disease posing a severe threat to global health. To date, sporadic studies have demonstrated that innate immune mechanisms, specifically neutrophilia, NETosis, and neutrophil-associated cytokine responses, are involved in COVID-19 pathogenesis; however, our understanding of the exact nature of this aspect of host–pathogen interaction is limited. Here, we present a detailed dissection of the features and functional profiles of neutrophils, dendritic ce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

23
152
1
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 128 publications
(177 citation statements)
references
References 59 publications
(73 reference statements)
23
152
1
1
Order By: Relevance
“…Studies show the importance of cytotoxic CD8 + T-cells in controlling primary SARS-CoV-2 infections. In other words, the increase of cytokines such as IL-10, IL-6 and TNF-α in these patients and their role in reducing T-cells worsens the disease's condition [ 62 ]. New therapies for the cure of COVID-19 patients could be fundamental approaches such as targeting the pathways of immunosuppressive adjusting molecules like Tim-3, PD-1, increasing cellular immune functions by increasing T-cell and NK cell counts, and functions, not only in the treatment of cancer, but also, in the face of respiratory infections [ 38 , 63 ].…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…Studies show the importance of cytotoxic CD8 + T-cells in controlling primary SARS-CoV-2 infections. In other words, the increase of cytokines such as IL-10, IL-6 and TNF-α in these patients and their role in reducing T-cells worsens the disease's condition [ 62 ]. New therapies for the cure of COVID-19 patients could be fundamental approaches such as targeting the pathways of immunosuppressive adjusting molecules like Tim-3, PD-1, increasing cellular immune functions by increasing T-cell and NK cell counts, and functions, not only in the treatment of cancer, but also, in the face of respiratory infections [ 38 , 63 ].…”
Section: Resultsmentioning
confidence: 99%
“…It has been suggested that, changes in the PD-1/PD-L1 pathway in chronic viral infections, like the human immunodeficiency virus (HIV), indicate the rearrangement of monocytes and dendritic cells (DCs) by signal transducer and activator of transcription 3 (STAT3)-dependent IL-10 production in response to the viral infection [ 42 , 43 ]. Moreover, elevated IL-10 levels in COVID-19 patients may also indicate the role of the PD-1/PD-L1 axis in the development of acute viral infections and monocyte rearrangement [ 44 ]. Neutrophils of the patients with COVID-19 are not able to regulate the expression of PD-L1 on the surface of immune cells compared to a healthy individual, so the levels of PD-L1's expression in these patients is low.…”
Section: Programmed Cell Death Protein 1 (Pd-1)mentioning
confidence: 99%
See 3 more Smart Citations